Crafting Inconspicuous Luxury Brands Through Brand Authenticity in China - Wu, Zhiyan (Frontiers in Psychology, 2022)
Currently, we are witnessing a trend toward subtle or absent hints of luxury, reflecting the rise of inconspicuousness. We seek to address why and how Chinese luxury brand managers, instead of matching conspicuous branding of many Western brands, develop inconspicuous strategies and craft authentic attributes in their brand communication. In the Chinese luxury brand context, we use the ethnographic research method with in-depth interviews, field visits, and photographs of eight Chinese luxury brands with inconspicuous preferences to reveal three main themes contributing to inconspicuousness. First, an inconspicuous approach of Chinese luxury brands is derived from the rise of inconspicuous consumption in China and a rejection of status brands due to being less famous than well-known Western brands, superficiality of status branding, and limited production capability. Second, we argue that inconspicuous branding can encompass developing luxury brands that avoid overtly displaying wealth and social status. Third, we identify three ways of crafting brand authenticity to build inconspicuous brands by using (a) nature to craft quality commitment dimension of authenticity (places and rare raw materials); (b) traditional Chinese craftsmanship and symbols to craft heritage dimension of authenticity; and (c) sincere stories (of how innovations are used in traditional craftsmanship), and the use of sustainability (sustainable raw materials, traditional craftsmanship, luxury production process, and saving resources) to craft sincerity dimension of authenticity in developing inconspicuous brands.